2017
DOI: 10.1101/180422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence ofMycoplasma genitaliumin different population groups: systematic review and meta-analysis

Abstract: BackgroundMycoplasma genitalium is a common cause of non-gonococcal non-chlamydial urethritis and cervicitis. Testing of asymptomatic populations has been proposed, but prevalence rates in asymptomatic populations are not well established. We aimed to estimate the prevalence of M. genitalium in adults in the general population, in clinic-based samples, pregnant women, men who have sex with men (MSM) and female sex workers (FSW). without language restrictions. We included studies with 500 participants or more. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 74 publications
(63 reference statements)
0
22
0
1
Order By: Relevance
“…[18 19] A review of the prevalence of M. genitalium has been published. [8] We report our findings according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA, online supplementary file 1). [20]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18 19] A review of the prevalence of M. genitalium has been published. [8] We report our findings according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA, online supplementary file 1). [20]…”
Section: Methodsmentioning
confidence: 99%
“…[7] In sex workers, men who have sex with men (MSM) and clinic-based populations prevalence was higher and more variable. [8] The increasing availability of nucleic acid amplification tests (NAAT) that detect M. genitalium has resulted in calls for widespread testing of asymptomatic populations. [9] But increased testing and treatment is likely to exacerbate the already high proportion of antimicrobial resistant M. genitalium, since de novo resistance to macrolides emerges rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in NAAT diagnostics and antibiotic resistance have inspired greater M. genitalium epidemiology studies that are gathered in the systematic review and meta-analysis by Baumann et al 7. This systematic review pored over 3000 citations and identified 117 studies that examined the prevalence of M. genitalium.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Estimated annual incidence rates of 12.0 million infections for Chlamydia trachomatis, 11.4 million for Neisseria gonorrhoeae and 37.4 million for Trichomonas vaginalis are reported for the African region [2]. Also, prevalence of Mycoplasma genitalium of up to 10% has been reported in studies from various countries in this region [3,4]. Adequate treatment for STIs is important, since untreated STIs can lead to pelvic inflammatory disease, adverse pregnancy outcomes and an increased risk of transmitting and acquiring human immunodeficiency virus (HIV) [5,6].…”
Section: Introductionmentioning
confidence: 98%